MiRNA‐106a and prostate cancer radioresistance: a novel role for LITAF in ATM regulation. Issue 8 (14th June 2018) - Hoey, Christianne; Ray, Jessica; Jeon, Jouhyun; Huang, Xiaoyong; Taeb, Samira; Ylanko, Jarkko; Andrews, David W.; Boutros, Paul C.; Liu, Stanley K.
Abstract : Recurrence of high‐grade prostate cancer after radiotherapy is a significant clinical problem, resulting in increased morbidity and reduced patient survival. The molecular mechanisms of radiation resistance are being elucidated through the study of microRNA (miR) that negatively regulate gene expression. We performed bioinformatics analyses of The Cancer Genome Atlas (TCGA) dataset to evaluate the association between miR‐106a and its putative target lipopolysaccharide‐induced TNF‐α factor (LITAF) in prostate cancer. We characterized the function of miR‐106a through in vitro and in vivo experiments and employed transcriptomic analysis, western blotting, and 3′UTR luciferase assays to establish LITAF as a bona fide target of miR‐106a. Using our well‐characterized radiation‐resistant cell lines, we identified that miR‐106a was overexpressed in radiation‐resistant cells compared to parental cells. In the TCGA, miR‐106a was significantly elevated in high‐grade human prostate tumors relative to intermediate‐ and low‐grade specimens. An inverse correlation was seen with its target, LITAF. Furthermore, high miR‐106a and low LITAF expression predict for biochemical recurrence at 5 years after radical prostatectomy. miR‐106a overexpression conferred radioresistance by increasing proliferation and reducing senescence, and this was phenocopied by knockdown of LITAF. For the first time, we describe a role for miRNA in upregulating ATM expression. LITAF, not previously attributed to radiation response, mediates this interaction. This route of cancer radioresistance can be overcome using the specific ATM kinase inhibitor, KU‐55933. Our research provides the first report of miR‐106a and LITAF in prostate cancer radiation resistance and high‐grade disease, and presents a viable therapeutic strategy that may ultimately improve patient outcomes. Abstract : We expand the current knowledge of the underpinnings of prostate cancer radioresistance. Using our well‐characterised radiation‐resistant cell line, we discovered two novel modulators of radioresistance, miR‐106a and its target LITAF, which act to increase proliferation and decrease senescence by upregulating ATM. We identify the specific ATM kinase inhibitor, KU‐55933, as a potential therapeutic intervention to resensitize radioresistant prostate cancer.